Evaluasi dan Perbaikan Alur dan Navigasi pada Website Jurusan Teknik Pengairan Universitas Brawijaya Menggunakan Metode Goal-Directed Design - Shafira Fitrianissa; Hanifah Muslimah Az-Zahra; Yusi Tyroni Mursityo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The Department of Water Engineering, Faculty of Engineering, Brawijaya University has three courses, namely Bachelor Program, Master Program, and Doctoral program. They used websites as a medium to deliver information for their academicians. In this research, the author will be focused on the problem of website sections for Water Engineering Undergraduate students found based on interviews and requirement. The obtained problem such as the users have difficulty to finding information because the presentation and the content's location on the website is not well organized and the website is still not user friendly. There is also a need to add the content on the website. Based on the problems, an initial test conducted with the tree testing method in order to assess the current structure of the website's information. The next step is a card sorting process to rearrange the information structure and represent them as a sitemap. Then another tree testing process conducted to reassuring that the new structure information reached users expectation. In this research we are applying the Goal-Directed Design method and the principle of Information Architecture and University Websites: Top 10 Guidelines to provide a recommendation such as a new redesign structure information (sitemap) and design to the website. In the final evaluation of user interface solution design we use the Single Ease Question (SEQ) questionnaire. The results of the final evaluation show that the design solution that has been made has received good responses from stakeholders and users.